Data base of Indian economy : review and appraisal, vol. 1 - Rao, C. Radhakrishna; Indian Econometric Society (Calcutta : Statistical Pub. Society and Indian Econometric Society, 1972)
This is the first of a series of seminars on the "Data Base of Indian Economy". Five areas are selected for discussion: Agriculture, Industry, Exports and Imports, Savings and Investment, and National Income. It is planned to cover other subjects like Population, Health, Education, etc. in subsequent seminars.
Organized by the Indian Econometric Society, Hyderabad.
Includes bibliographical references.
rpm 20/09/2017
Loans
Keywords: Statistical services; Economic history; India